PREPARATION AND MOLECULAR STRUCTURE OF BIS (TETRAMETHYLETHYLENEDIAMINE) COPPER(I) DICHLORO CUPRATE(I) , [Cu (TMEDA) ] [CuC1 ] (Journal of Sciences, Islamic Republic of Iran)
A complex of N, N, N', N', -tetramethylated ethylenediamine, TMEDA, with CuCI is prepared. The crystal and molecular structure of this complex is characterized by a single-crystal X-ray diffraction study. The complex is found to contain [Cu (TMEDA) ] cation which is nearly tetrahedral and the [CuCI ) anion is linear which Cu lies on a center of symmetry. Crystals are monoclinic space group P2 / n with four molecules/ unit cell of dimensions a = 9.240 (4), b = 14.930 (3), c = 14.288 (5) ? and B= 97.02 (3)?. The final R value is 0.045 for 3808 reflections measured.